Influence of irrigation regimes and weed management practices on water use and nutrient uptake in wheat (Triticum aestivum L. emend. Fiori and Paol.) - Verma, SK; Singh, SB; Prasad, SK; Meena, RN; Meena, RS (Bangladesh Journal of Botany, 2018)
A field experiment was conducted in sandy clay loam soil during winter season of 2012-13. The lowest weed dry weight and the highest nutrient content were recorded under 80 mm CPE. Significantly the highest grain and straw yield, total nutrients uptake, and the highest consumptive use of water (57.8 cm), rate of water use (4.52 mm/day), water use efficiency (87.3 kg/ha-cm) and soil profile moisture was extracted with irrigation at 40 mm CPE. Application of sulfosulfuron recorded significantly lowest weed biomass and the highest nutrient content and their uptake, grain and straw yield, and maximum consumptive use of water (51.5 cm), rate of water use (4.02 mm/day), water use efficiency (91.3 kg/ha-cm) and soil profile moisture extraction over metribuzin and it was at par with metsulfuron-methyl. Grain (6.57 kg/ha) and straw yield (12.3 kg/ha) will be reduced by an increased in unit dry matter production in weeds.